RECONCEPTUALIZATION OF COMMUNICATIVE APPROACH IN LANGUAGE TEACHING: ITS IMPLICATION ON TEACHER’S COMPETENCE AND ENVIRONMENT SUPPORT SYSTEM - Ferlya Elyza; Rini Susiani (Jurnal Dedikasi Pendidikan, 2023)
This article provides a brief discussion of the four topics related to the Communicative Approach (CA) theme in English language teaching and its implication for teachers’ competence and environmental support system. The communicative approach, communicative competence, CA’s implication on language teaching and teacher’s competence, and the learning environment support are connected in a brief overview. CA, or familiarized with communicative language teaching terminology, was proposed by Savignon& Berns in the late 1960s, and it developed in the mid of 1970s with the popular name of CA (communicative approach). The first coin of CA is how it closely engages in the process of English language teaching. The goal is to prepare English language learners to be highly competent in teaching and communicating skills to face the global era. Students are able to develop their four language teaching skills. A conducive and supportive learning environment is the support system in applying CA to support the four language skills. As a result, CA’s implication in language teaching, particularly English, is to enhance language learners’ communicative competencies.